TO THE INTERPRETATION OF THE LIMITS OF APPLICATION OF THE CRIMINAL CODE OF THE REPUBLIC OF MOLDOVA IN THE FIELD OF COUNTERING EXTREMIST ACTIVITIES - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Sociale)
The purpose of this scientific article is to report issues of law enforcement in the field of combating extremist activity (verbal or physical) in the current legislation of the Republic of Moldova, indicating the limits of liability for crimes and violations provided for the Criminal Code and the Code of contraventions, correspondingly. As a result of the scientific research, the following steps were taken in the field of combating extremism: an attempt was made to identify and independently classify extremist activities by comparing the provisions of the Law of the Republic of Moldova No. 54/2003, on the one hand, and the Code of Offenses and the Criminal Code of the Republic of Moldova, on the other hand; the close interaction between the motive of prejudice and the extremist motive has been substantiated, where prejudice serves as the foundation of radicalism, extremism and even terrorism; the similarities and differences between extremist and hooligan motives have been proven; conclusions and recommendations aimed at improving modern legal doctrine and legislation have been formulated. Keywords: extremist activity; fanaticism; fundamentalism; extremism; radicalism; terrorism; terrorist activity; reason for prejudice; the extremist motive; extremist materials; propaganda; agitation; call.